(untitled) (Revista Apotheke, 2019)
The paper discuss some of the characteristics that compose the draw and the painting; how these two languages relate to each other and where they differ. The text is based on the writings of the philosopher Roland Barthes, where he analyses Cy Twombly work from 1961 to 1979, and is based on Walter Benjamin essay of 1917, that presents the elements of painting and drawing in a disjunctive way. Both reflections explore aspects like the stain, the support, the stroke, inscriptions and graphisms. Barthes comments on elements that are present in Twombly’s paintings that could be considered exclusive in the drawing collection. From the approaches presented by the philosophers it is intended to promote a debate about these two languages, to discuss about the specificities of each one, and to reflect about how those characteristics are showed in the more recent art.